(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Diabetes mellitus is a chronic metabolic disorder classified into Type 1 and Type 2, each with distinct pathophysiological mechanisms, clinical courses, and diagnostic criteria. Type 1 diabetes (T1DM) is an autoimmune condition characterized by the destruction of pancreatic beta cells, leading to absolute insulin deficiency and a sudden onset of symptoms, often in childhood or adolescence. In contrast, Type 2 diabetes (T2DM) develops gradually due to insulin resistance and progressive beta-cell dysfunction, typically affecting adults and strongly associated with obesity and lifestyle factors. The clinical course of T1DM involves a high risk of diabetic ketoacidosis (DKA), while T2DM is often asymptomatic in its early stages but can lead to long-term complications such as cardiovascular disease. Diagnosis of both types relies on blood glucose measurements, but distinguishing features include the presence of autoantibodies and low C-peptide levels in T1DM, while T2DM is often characterized by elevated C-peptide and insulin levels in the early stages. Understanding these differences is crucial for accurate diagnosis, appropriate management, and effective prevention strategies.